Theorizing Digital Platforms: A Conceptual Framework for the Gig Economy - Shevchuk, Andrey (Journal of Economic Sociology, 2023)
Contemporary sociology of work pays increasing attention to the study of the work experiences of individuals engaged in digital labour platforms. However, for a deeper understanding of the gig economy, this approach needs to be complemented by an analysis of the digital platforms as organizational structures and social actors. This article proposes a conceptual framework for such analysis, drawing on theoretical insights from economic sociology, institutionalism, and political economy. The role of digital platforms is problematized through the five key categories (organizational innovation, mediator, market infrastructure, private regulator, institutional entrepreneur), which are systematically integrated into the analysis. Digital platforms represent a radical organizational innovation built on technologies capable of effectively coordinating the activities of dispersed agents without requiring their spatial, temporal, or organizational co-presence. This facilitates the growth of businesses benefiting from the mediation of external workers and resources. The communication means facilitated by platforms gradually transform into systemic infrastructure, shaping the fundamental conditions for market functioning. With the ability to unilaterally establish “rules of the game” and exercise algorithmic control, platforms evolve into private market regulators, competing with the state. To strengthen and legitimize their power, platforms actively engage in the political process with the aim of social market reorganization and overall institutional restructuring. At this stage, the conceptual framework loops back to the idea that platforms represent an innovation, the diffusion of which must address the most acute social contradictions related to the role of platforms as mediators, infrastructures, private regulators, and institutional entrepreneurs. The article demonstrates how the proposed categories can be applied to the analysis of various gig economy issues.